2023
DOI: 10.1126/sciadv.adc9465
|View full text |Cite|
|
Sign up to set email alerts
|

Lactate promotes endothelial-to-mesenchymal transition via Snail1 lactylation after myocardial infarction

Abstract: High levels of lactate are positively associated with the prognosis and mortality in patients with heart attack. Endothelial-to-mesenchymal transition (EndoMT) plays an important role in cardiac fibrosis. Here, we report that lactate exerts a previously unknown function that increases cardiac fibrosis and exacerbates cardiac dysfunction by promoting EndoMT following myocardial infarction (MI). Treatment of endothelial cells with lactate disrupts endothelial cell function and induces mesenchymal-like function f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 67 publications
1
61
0
Order By: Relevance
“…Lactylation is a post‐translational modification, exerting functions in various biological processes 22,23 . Here, we investigated whether the SCO altered protein lactylation in PDLSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Lactylation is a post‐translational modification, exerting functions in various biological processes 22,23 . Here, we investigated whether the SCO altered protein lactylation in PDLSCs.…”
Section: Resultsmentioning
confidence: 99%
“…The latest research shows that treating endothelial cells with lactate can activate TGF β/Smad2 pathway which disrupts endothelial cell function and promotes the phenotypic transition from endothelial cells to mesenchymal cells. Such changes exacerbate the risk of myocardial infarction (Fan et al, 2023).…”
Section: Lactate Lactylation and Wound Healingmentioning
confidence: 99%
“…Recently, lactylation, a novel PTMs (Zhang et al 2019), has played an important role in neuroregulation(Hagihara et al 2021), endothelial‐to‐mesenchymal transition (EndoMT) (Fan et al 2023), tumor immunity (Xiong et al 2022), and tumor metabolism (Wang et al 2022; Yang et al 2023). The authors used two online databases of lysine lactylation (Kla) (Lai and Gao 2023; Meng et al 2022) to predict the presence of lactylation sites in human IL‐33 (data not shown).…”
Section: Post‐translational Modifications and Functional Changes Of N...mentioning
confidence: 99%